New Non-toxic Iron Chelators SP9 and SP10 and Its Potentiality as Brain Supplement - Nishida, Yuzo (Brain Supplement, 2019)
Nishida has succeeded in synthesizing the novel iron chelators, which are shown to be non-toxic with reduced side effects, named as Super-polyphenols, and two examples of water-soluble super-polyphenol, SP9 and SP10, are illustrated in Figure 1. The non-toxicity of these compounds exemplified by Ohara et al. should be due to that these compounds cannot be a substrate for cytochrome P450 because of its hydrophilicity, and also to that the iron (III)-chelates of these super polyphenols are non-toxic, which is strongly supported by the studies on the chemical mechanism of the toxicity induced by the iron (III) with artificial chelates in human body done by Nishida [1,5,6]; the most important point is that these two chelators do not form a dangerous micro-oxo bridged dimeric iron (III) species. In addition to these, oral administration of SP10 and SP9 are shown to inhibit tumor growth in vivo in an HCT116 and A549 xenograft models (nude mouse), respectively. According to Tomono et al., the anti-tumor effect of Exjade (Deferasirox) on A549 xenograft model was almost the same as that of SP9 under the same experimental conditions. Drs. Okuda and Sugimoto at Doshisha University have administrated orally SP9 and SP10 in the drinking water (0.5 %) for 9 weeks to the APP/PS1 transgenic mouse with brain where excess amyloid beta-proteins are present to form senile plaques, and found that none of 18 mice died after administration of SP9 and SP10, although two of 9 mice died in the control system without SP9 or SP10, implying that the presence of SP9 or SP10 depresses the toxicity due to the amyloid beta-proteins. All the above facts are suggesting that new non-toxic iron chelator SP10 can be a good oral brain supplement, and we can supply SP10 to all the researchers who want to use SP10 for their studies.